Sistem Informasi Geografis Pemetaan Jumlah Kendaraan Bermotor Dan Tingkat Emisi Karbon Di Jawa Barat - Ashari, Rifda Arifah; Herlambang, B.A.; Anam, A.Khoirul (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
The increase in the number of motorized vehicles in various regions of Indonesia has a direct impact on the high carbon emissions produced from the fossil fuel burning process. Carbon emissions are one of the main contributors to air pollution and also have an impact on accelerating global warming. This study aims to analyze the relationship between the numberof motor vehicles and the level of carbon emissions in the West Java region using the Geographic Information System (GIS) approach. Through the integration of spatial and non-spatial data, the system is designed to map the distribution of motor vehicles, calculate carbon emission estimates, and present thematic maps depicting areas with high emission levels. The results of this study are expected to be able to provide accurate visual information about the pattern of carbon emission distribution, so that it can be a reference for sustainable transportation policy making.